Association between sun-protective behaviors and hypertension: a cross-sectional study from National Health and Nutrition Examination Survey 2009 to 2014 - Shuping Yang; Feng Dai; Zhaokai Wang; Ruoshui Li; Xianzhi Xu; Cheng Li; Xiancun Hou; Yang Liu; Chaofan Wang; Dongye Li; Lei Li; Tongda Xu (BMC, 2023)
Abstract Background In previous studies, sun-protective behaviors increased cardiovascular incidence. Our present article is to further analyze the potential relationship between sun-protective behaviors (staying in the shade, wearing long-sleeved clothing, and applying sunscreen) and hypertension. Method The present cross-sectional study evaluated 8,613 participants (aged 20-60 years) from the National Health and Nutrition Examination Survey (NHANES) obtained between 2009 and 2014. We performed multiple logistic regression analysis to examine the relationship between sun-protective behaviors and hypertension. Subgroup analysis was then performed. Multiple linear regression analysis was utilized to examine the relationship of sun-protective behaviors and each sun-protective behavior with systolic and diastolic blood pressure, stratified by sex and race. Results A total of 8,613 participants (weighted n = 127,909,475) were applied in our study, including 1,694 hypertensive subjects. Our study demonstrated that sun-protective behaviors of the 2-3 category were associated with increased risk of hypertension, but not with higher systolic and diastolic blood pressure. In subgroup analysis, men, Mexican American, and 25 < BMI ≤ 30 who reported sun-protective behaviors (2-3) were prone to hypertension. Multiple linear regression models showed that non-Hispanic white men with sun-protective behaviors (2-3) were positively associated with systolic and diastolic blood pressure. The association between other-Hispanic men with frequent wearing long-sleeved clothing and diastolic blood pressure was positively correlated. Conclusion Sun-protective behaviors of the 2-3 category could increase the incidence of hypertension, but not increase systolic and diastolic blood pressure. We only found that non-Hispanic white men who reported sun-protective behaviors (2-3) were positively associated with systolic and diastolic blood pressure. These findings suggested that excessive sun-protective behaviors should be avoided.